2016
DOI: 10.1101/lm.042531.116
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency stimulation-induced synaptic potentiation in dorsal and ventral CA1 hippocampal synapses: the involvement of NMDA receptors, mGluR5, and (L-type) voltage-gated calcium channels

Abstract: The ability of the ventral hippocampus (VH) for long-lasting long-term potentiation (LTP) and the mechanisms underlying its lower ability for short-lasting LTP compared with the dorsal hippocampus (DH) are unknown. Using recordings of field excitatory postsynaptic potentials (EPSPs) from the CA1 field of adult rat hippocampal slices, we found that 200-Hz stimulation induced nondecremental LTP that was maintained for at least 7 h and was greater in the DH than in the VH. The interaction of NMDA receptors with L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 54 publications
(63 reference statements)
0
11
1
Order By: Relevance
“…Strikingly, this difference was found to be almost faded away in middle-aged (9–12 months old) animals, apparently due to a decline in strength of ventral LTP to a similar magnitude as dorsal LTP. The larger ventral DG-LTP is diametrically opposed to studies in the CA1 region, where the dorsal segment has been reported to have a higher ability to undergo LTP 10 14 . In accordance with a dorsoventral gradient rather than a clear-cut segregation, our LTP data of the intermediate segment fall right in between those of dorsal and ventral slices, supporting the presence of an intermediate region that expresses “partly overlapping characteristics with its neighbour regions”, as proposed by Fanselow and Dong (2010) 1 .…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Strikingly, this difference was found to be almost faded away in middle-aged (9–12 months old) animals, apparently due to a decline in strength of ventral LTP to a similar magnitude as dorsal LTP. The larger ventral DG-LTP is diametrically opposed to studies in the CA1 region, where the dorsal segment has been reported to have a higher ability to undergo LTP 10 14 . In accordance with a dorsoventral gradient rather than a clear-cut segregation, our LTP data of the intermediate segment fall right in between those of dorsal and ventral slices, supporting the presence of an intermediate region that expresses “partly overlapping characteristics with its neighbour regions”, as proposed by Fanselow and Dong (2010) 1 .…”
Section: Discussioncontrasting
confidence: 59%
“…Furthermore, the subunits of AMPA and NMDA glutamate receptors, important postsynaptic components in synaptic plasticity, are differentially distributed along the dorsoventral axis in the rat hippocampus 23 . Several other channels that are important for intrinsic excitability are also differentially expressed or activated along the dorsoventral axis 14 , 24 27 . This results in decisive differences in neuronal parameters which control the excitability and firing properties, and hence the basal input/output properties and LTP magnitude obtained in response to particular induction protocols 13 , 25 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, a classic in vitro model was established for investigating LTP based on the acute hippocampal slice, which is widely used due to its simplified neural circuits and relatively easy recording of extracellular synaptic responses. Using the classic model, a variety of mechanistically motivated experiments that were not feasible in vivo were performed [5]. It is now understood that the underlying mechanisms of LTP relate to the NMDA (N-methyl-D-aspartate) and AMPA (a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid) receptors [5].…”
Section: Introductionmentioning
confidence: 99%
“…Using the classic model, a variety of mechanistically motivated experiments that were not feasible in vivo were performed [5]. It is now understood that the underlying mechanisms of LTP relate to the NMDA (N-methyl-D-aspartate) and AMPA (a-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid) receptors [5]. The basic properties of LTP, including cooperativity, synaptic specificity and associativity, are found to fit well with Hebb's postulate and can be explained by the biophysical properties of the NMDA receptor that is needed to trigger LTP [6].…”
Section: Introductionmentioning
confidence: 99%
“…With respect to electrophysiological properties, there are distinct differences between dorsal and ventral CA1 pyramidal neurons in basic membrane parameters and excitability (e.g., input resistance, resting membrane potential) [15]. Long term potentiation (LTP) is stronger in the dorsal hippocampus, and this is correlated with a higher density of NMDA receptors, higher NMDA-mediated field excitatory postsynaptic potentials [16], and a more effective interaction between NMDA receptors and L-type voltage dependent calcium channels [17]. Furthermore, in the RNA-seq database of gene expression in hippocampal neurons [18], a number of genes in a gene cohort associated with LTP exhibited increased expression in dCA1 neurons relative to vCA1 neurons.…”
Section: Introductionmentioning
confidence: 99%